"When once you have fallen into an equable stride": The Peripatetic in Vaughan Williams's Songs of Travel. Issue 4 (2nd October 2017) - Leistra-Jones, Karen
ABSTRACT: Vaughan Williams's cycle Songs of Travel reveals implications of walking as an embodied cultural practice. The cycle follows a vagabond character as he sets out on foot in pursuit of spiritual and artistic wisdom. Walking was a ubiquitous form of recreation in Vaughan Williams's social milieu, and many authors in the preceding decades had explored the subject at length. Their efforts helped to codify what Anne D. Wallace (1993) has termed "peripatetic theory, " which asserts that there are certain physical, perceptual, and spiritual experiences only possible by means of foot travel. Placing Vaughan Williams's music in dialogue with other peripatetic texts shows how walking—as an experience and a discourse in Victorian and Edwardian Britain—informed both individual songs and the narrative structures underlying the cycle.